1981
DOI: 10.1172/jci110123
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone Prevention of Increased Lung Vascular Permeability following Endotoxemia in Sheep

Abstract: A B S T R A C T To see whether methylprednisolone would affect the pulmonary vascular response to endotoxemia, we studied responses to endotoxemia in the presence and absence of methylprednisolone in the same chronically instrumented, unanesthetized sheep. Infusion of Escherichia coli endotoxin (0.70-1.33,g/ kg) caused an initial period of marked pulmonary hypertension followed several hours later by a long period of increased vascular permeability when pulmonary vascutlar presstures were niear base linie (bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…The initial phase of pulmonary hypertension is prevented by indomethacin given before and after the infusion of bacteria. The later phase is not affected by indomethacin, yet.is prevented by steroids (8,9). In addition, recent evidence suggests that the increase in pulmonary hypertension and PVR and the decrease in CO noted in this late phase of GBS sepsis are reversed by a leukotriene antagonist (2,10).…”
Section: Discussionmentioning
confidence: 96%
“…The initial phase of pulmonary hypertension is prevented by indomethacin given before and after the infusion of bacteria. The later phase is not affected by indomethacin, yet.is prevented by steroids (8,9). In addition, recent evidence suggests that the increase in pulmonary hypertension and PVR and the decrease in CO noted in this late phase of GBS sepsis are reversed by a leukotriene antagonist (2,10).…”
Section: Discussionmentioning
confidence: 96%
“…Increased Pw in the control experiments most likely resulted from a general vasoconstriction throughout the lung. Left heart failure was ruled out, since left atrial pressure has been found to be unchanged or reduced by endotoxin infusion (3,30). Inhibition of TxA2 synthesis by dazoxiben essentially prevented increased Ppa, Pw, and PVR after endotoxin infusion, even though the vasoconstrictor PGF2a concentration was elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Lung oedema (dry: wet weight ratios) was more clearly reversed by the steroids. Such antagonism of the effects of endotoxin are well known for methylprednisolone (Al-Kaisi et al, 1977;Brigham et al, 1981;Borg et al, 1985b) and, although relatively less substantiated for budesonide (Ottosson et al, 1986), it would be expected from budesonide's generally anti-inflammatory profile of activities (Kallstrom et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…there is considerable experimental evidence that corticosteroids antagonize or prevent lung injury due to endotoxaemia (Al-Kaisi et al, 1977;Hinshaw et al, 1980;Brigham et al, 1981;Schumer, 1981;Borg et al, 1985b), we have also looked at the effects of two synthetic corticosteroids, methylprednisolone and budesonide, on our model of endotoxin-induced lung injury. A preliminary account of some of this work has been given to the British Pharmacological Society (Izumi & Bakhle, 1987).…”
Section: Introductionmentioning
confidence: 99%